1, 2‐Carboboration of Arylallenes by In Situ Generated Alkenylboranes for the Synthesis of 1, 4‐Dienes. Issue 32 (21st April 2022) - Averdunk, Arthur; Hasenbeck, Max; Müller, Tizian; Becker, Jonathan; Gellrich, Urs
Abstract: We herein report a novel method for the coupling of unactivated alkynes and arylallenes, which relies on an unprecedented and regioselective 1, 2‐carboboration of the allene by an alkenylborane. The alkenylborane is conveniently prepared in situ by hydroboration of an alkyne with Piers' borane, i. e ., HB(C6 F5 )2 . The boryl‐substituted 1, 4‐dienes that are formed by this carboboration are well‐suited for a subsequent Suzuki‐Miyaura coupling with aryl iodides. This allowed us to develop a three‐step, one‐pot protocol for the synthesis of aryl‐substituted 1, 4‐dienes. The generality of the reaction was demonstrated by the synthesis of twenty dienes with modular variations of all three reaction partners. The mechanism of the new 1, 2‐carboboration was investigated using dispersion corrected double‐hybrid DFT computations that allowed us to rationalize the chemo‐ and regioselectivity of this key step. Abstract : A chemo‐ and regioselective 1, 2‐carboboration of arylallenes by alkenylboranes, formed in situ by hydroboration of alkynes with Piers' borane (HB(C6 F5 )2 ) is reported. This novel 1, 2‐carboboration and a subsequent Suzuki‐Miyaura coupling were used for the synthesis of twenty new aryl substituted 1, 4‐dienes.